2009
DOI: 10.1093/ntr/ntp092
|View full text |Cite
|
Sign up to set email alerts
|

Urine nicotine metabolite concentrations in relation to plasma cotinine during low-level nicotine exposure

Abstract: Measurement of urine cotinine corrected for creatinine concentration appears to be the best predictor of plasma cotinine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 14 publications
5
77
0
1
Order By: Relevance
“…These metabolites are excreted in urine primarily [25]. Urinary levels of cotinine are higher than that of the blood levels [26]. Studies in animals showed a dose-dependent increase in cotinine levels in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites are excreted in urine primarily [25]. Urinary levels of cotinine are higher than that of the blood levels [26]. Studies in animals showed a dose-dependent increase in cotinine levels in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the demonstration of these adverse effects of secondhand smoke exposure, 40% of Americans are still exposed to secondhand smoke, including 54% of children between ages 3 and 11 years (35). In some of our analyses, we dichotomized passive smokers at the median into low-level (,0.19 ng/ml) and moderate-to high-level (>0.19 ng/ml) exposure; a plasma cotinine level of 0.20 ng/ml is roughly equivalent to spending 1 hour in a moderately smoky room, such as a bar or restaurant (43,44). Thus, the quantity of passive smoke exposure associated with increased risk of ALI in this study appears to be relatively modest, although this threshold for exposure will need to be further tested in other at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison purposes, researchers must consider whether free cotinine or total (free plus conjugated) cotinine was measured. Free cotinine is preferable to use as it correlates better with plasma cotinine than total cotinine 7. Current state-of-the-art methods are GC-MS/MS and LC-MS/MS, with limits of detection (LOD) of 0.05 ng/ml,20 21 a sensitivity concentration needed in countries with low SHSe due to clean air regulations and lower air nicotine concentrations.…”
Section: Analytical Methods For Biomarkers Of Shsementioning
confidence: 99%
“…Blood's cotinine concentrations and saliva are highly correlated. Urine cotinine concentrations average fourfold to sixfold higher than those in blood or saliva, making urine a more sensitive matrix to detect low-concentration exposure 7. Six metabolites (nicotine, cotinine and trans-3â€Č-hydroxycotinine (3-HC) and their respective glucuronide conjugates) account for about 85% to 90% of a nicotine dose, and the sum of these metabolites in urine provides an approximate estimate of daily nicotine intake.…”
Section: Selection Of Biomarkers Of Shsementioning
confidence: 99%